ZeroMAC: Toward a zero sleep delay and zero idle listening media access control protocol with ultralow power radio frequency wakeup sensor. (August 2017) - Lee, Sang Hoon; Choi, Lynn
In wireless sensor networks, duty cycling has been an imperative choice to reduce idle listening but it introduces sleep delay. To break through the energy-latency tradeoff, we propose a pair of a radio wave sensor called radio frequency wakeup sensor and an on-demand media access control protocol called ZeroMAC. Radio frequency wakeup sensor is dedicated to sense the presence of a signal. The distinctive feature is that the sensor can provide the same sensitivity while it consumes only two orders of magnitude less energy than the underlying radio frequency module. With the sensor, a node no longer requires duty cycling. We also propose an on-demand media access control protocol called ZeroMAC that can effectively utilize the on-demand wakeup functionality of a radio frequency wakeup sensor by broadcasting a dedicated signal to wake up nodes before starting a communication. Since each node can notify neighbor nodes of a communication immediately, ZeroMAC can eliminate both idle listening and sleep delay. ZeroMAC wakes up only the nodes on the communication path by propagating wakeup signals in a hop-by-hop manner, avoiding unnecessary signal flooding. To further save energy, ZeroMAC can turn off radio frequency module as soon as it detects the end of communication. According to packet level simulation results, ZeroMAC can deliver data packets at least 1.87 times faster by eliminating both idle listening and sleep delay while it consumes only 3% of the energy compared to X-MAC and A-MAC.